Rosebud sleds and horses' heads 50 of film's most evocative objects - Harris, Scott Jordan (Intellect Books, The University of Chicago Press, 2013)
Dorothy's ruby slippers. Michael Myers' mask. Marilyn Monroe's billowy white dress. Indiana Jones' trusty hat. These objects are synonymous with the films they appear in and have become icons of popular culture. Rosebud Sleds and Horses' Heads sorts and chronicles fifty of them. It discusses the most significant objects in cinema history and explores their importance within their respective films and the popular imagination.